Enhanced UV–Vis Rejection Ratio in Metal/BaTiO3/β‐Ga2O3 Solar‐Blind Photodetectors - Nathan Wriedt; Lingyu Meng; Dong Su Yu; Chris Chae; Kyle Liddy; Ashok Dheenan; Sushovan Dhara; Roberto C. Myers; Oleg Maksimov; Richard Blakeley; Sanjay Krishna; Jinwoo Hwang; et al. (Advanced Electronic Materials)
Abstract The fabrication and characterization of metal/BaTiO3/β‐Ga2O3 solar‐blind photodetectors are reported. β‐Ga2O3 is a promising material for solar‐blind photodetectors due to its large bandgap and the availability of low defect‐density melt‐grown substrates. In this work, structures are introduced that employ high‐permittivity dielectric/semiconductor heterojunctions to enhance the performance of a Schottky photodetector. It is shown that integrating the high‐k dielectric BaTiO3 reduces the dark current by ≈104, all but eliminates illumination induced Schottky barrier lowering, and increases the UV–vis rejection ratio by a factor greater than 9 × 103 compared to a Schottky photodetector. It is hypothesized that the high permittivity of the dielectric overcomes the influence of self‐trapped holes in Ga2O3 to reduce the peak electric field at the dielectric/metal interface, thereby eliminating the effects of Schottky barrier lowering on illuminated β‐Ga2O3 photodetectors. Additionally, it is hypothesized that the increase in the UV–vis rejection ratio is caused by the “dead layer” that forms at the BaTiO3/Pt interface.